2017
DOI: 10.3892/mmr.2017.7609
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin ameliorates the progression of atherosclerosis in LDL receptor-deficient mice

Abstract: Previous studies have demonstrated that regulatory T cells (Tregs) are pivotal in the regulation of T cell-mediated immune responses in atherosclerosis, a chronic autoimmune-like disease. In the authors' previous studies, it was demonstrated that amygdalin ameliorated atherosclerosis by the regulation of Tregs in apolipoprotein E-deficient (ApoE−/−) mice. Therefore, the aim of the present study was to investigate the therapeutic effect of amygdalin on low-density lipoprotein (LDL) receptor deficient (LDLR−/−) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Amygdalin, which is also known as vitamin B17 or Laetrile ( Lv et al, 2017 ), is an aromatic cyanogenic compound that belongs to sub-class of carbohydrates and carbohydrate conjugates. Chemical formula of amygdalin is C 20 H 27 NO 11, having molecular weight of 457.432 g/mol and D-mandelonitrile-beta-D-gentiobioside structure ( Chang et al, 2006 ), as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Amygdalin, which is also known as vitamin B17 or Laetrile ( Lv et al, 2017 ), is an aromatic cyanogenic compound that belongs to sub-class of carbohydrates and carbohydrate conjugates. Chemical formula of amygdalin is C 20 H 27 NO 11, having molecular weight of 457.432 g/mol and D-mandelonitrile-beta-D-gentiobioside structure ( Chang et al, 2006 ), as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because the acid value of the oil was 50.6 KOH mg/g, the oil was determined to be unsuitable as food 15 . In addition, loquat seed contains amygdalin 4 , and is also known to be unsuitable as food for this reason. Therefore, hexane was used to extract the loquat seed oil.…”
Section: Characteristics Of Loquat Seed Oilmentioning
confidence: 99%
“…Loquat seeds are further used as a traditional medicine to treat cough and indigestion 2 . Amygdalin has been extensively studied as one of the primary active ingredients responsible for these pharmacological effects 4 . In addition to amygdalin, numerous studies have been conducted on other ingredients derived from loquat seeds, and their physiological effects have been elucidated 5 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one property of baicalin and geniposide ameliorating AS is ascribed to the gathering blockade of DCs in plaque areas that launch proatherogenic immune reactions [ 146 ]. Owing that regulatory T cells (Tregs) hinder T helper (Th) cells-induced inflammation, QSYQ and amygdalin increase the content of Tregs in vascular lesions which delay the development of AS [ 30 , 147 ]. Additionally, QSYQ directly inhibit Th17 cells in AS areas and then lower the release of IL-17, a proatherogenic cytokine [ 30 ].…”
Section: Mechanisms Of Action Of Chmsmentioning
confidence: 99%